Acquisition of Pedagogical Competencies by Librarians in Academic Libraries in Cameroon: Perceptions and Needs - Case Study. (International Journal of Scientific Research and Management (IJSRM), 2021)
The development of information and communication technologies is the cause of constant change in the librarian profession at the university in particular. Indeed, it is the best environment for research. Professionals adapt to the user-generated new needs as information mediators. It is in this sense that the continuing professional development of academic librarians at the University of Yaoundé I lies at the heart of this undertaking. Its implementation requires a regular needs assessment. The study highlights the pedagogical skills needs of the academic librarians. It identifies their strengths as to their qualifications to pass on knowledge about information research to target audiences, and develop skills within the library services. A grid of pedagogical skills needs was submitted to librarians who were able to express their needs. This resulted in interviews with library officials and academic libraries. The results of the study show great awareness of their pedagogical mission. Important initiatives have been taken in this area, but they need to be formalized, using appropriate tools for a greater efficiency. Suggestions are made in order to increase the visibility of academic libraries of the University of Yaoundé I among the faculties or institutions by bringing diverse actors together